Urinary Calculi: A Microbiological and Biochemical Analysis at a Tertiary Care Hospital in Eastern Nepal - Pratima Shah; Ratna Baral; C. S. Agrawal; Madhab Lamsal; Dharanidhar Baral; Basudha Khanal (International Journal of Microbiology)
Background. The occurrence of urinary tract infection in presence of urolithiasis is frequently noted; however, microbial agents of urolithiasis and their antimicrobial susceptibility patterns remain underinvestigated. This study aimed to identify the microorganisms isolated from urine and stone matrices to determine their antimicrobial susceptibility, to find the association between the pathogens of urine and stone matrices, and to perform the biochemical analysis of stones. Methods. A total of 88 cases of urolithiasis admitted for elective stone removal at Department of surgery, B.P. Koirala Institute of Health Sciences (BPKIHS), were enrolled. Preoperative urine culture and postoperative stone culture were performed. Isolation, identification, and AST were done by the standard microbiological technique. Further qualitative biochemical analysis of stones was also attempted. Result. Among 88 stone formers recruited, culture of urine, whole stone, and nidus yielded the growth of bacteria 44, 32, and 30, respectively. Bacteria isolated from urine culture correlated with those from stone matrices with a sensitivity of 90%, specificity of 79.69%, PPV of 63.64%, and NPV of 95.45%. Escherichia coli (46.7%) was the most common bacteria followed by Klebsiella pneumoniae (16.7%) and Proteus mirabilis (13.3%) from urine and stone cultures. Almost all the uropathogens isolated were susceptible to commonly used antibiotics. Calcium oxalate (84.1%) was common biochemical constituent found in stone formers followed by calcium oxalate + phosphate (8%). Conclusions. The association of microorganism isolated from urine and nidus culture was significant that can predict the source of infective stone; however, in some cases, microorganisms and the antimicrobial susceptibility pattern from urine and nidus were different. This study emphasizes the use of appropriate antimicrobial agents to prevent the regrowth of residual stones and minimize the risk of infectious complications after surgical removal of stones.